THE MEDIATING ROLE OF ORGANIZATIONAL LEARNING, AND DAPODIK INFORMATION TO OPTIMIZE THE ROLE OF SCHOOL PRINCIPALS, AND STUDENTS' MENTALITY TOWARDS TEACHER CERTIFICATION - Muhammad, Indra; Fadeli, Fadeli; Buheti, Buheti; Budi Wahyuni, Raden; Ilham Maliki, Budi (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Generally, teacher certification is limited to improving welfare, improving the quality of education and as proof of teacher performance. The aim of the research is to build a model of the involvement of other factors in teacher certification. This type of research is quantitative in the form of respondent data collected through distributing questionnaires to elementary school teachers who have received certification. The results of the research include 1) there is an influence of the role of the school principal on Dapodik information. 2) there is no influence of the principal's role on organizational learning. 3) there is a mental influence of students on Dapodik information. 4) there is an influence of student mentality on organizational learning. 5) there is an influence of Dapodik information on teacher certification. 6) there is an influence of organizational learning on teacher certification.